The influence of thyroid autoimmunity on embryo quality in women undergoing assisted reproductive technology. (2nd September 2018) - Andrisani, A.; Sabbadin, C.; Marin, L.; Ragazzi, E.; Dessole, F.; Armanini, D.; Donà, G.; Bordin, L.; Ambrosini, G.
Abstract: The influence of thyroid autoimmunity in assisted reproductive technology (ART) outcome in euthyroid women is still controversial. In this study, we retrospectively evaluated embryo quality in 123 euthyroid women undergoing ART with or without thyroid autoantibodies (TAA). Embryo quality was assessed in 119 embryos of 29 infertile patients with TAA and in 394 embryos of 94 infertile patients without TAA. Our results showed not statistically significant differences in age, body mass index, anti-Müllerian hormone, follicle stimulating hormone, free triiodothyronine, and free thyroxine levels between cases and controls. Thyroid stimulating hormone was within the normal range, but significantly higher in TAA patients compared with the controls (2.4 ± 0.8 vs. 2 ± 0.9 mIU/L, respectively, p < .01). The number of oocytes picked up and fertilized was comparable between the two groups. Embryo quality was significantly impaired in women with at least one autoantibody ( p < .001). Implantation rate, pregnancy rate, and ongoing pregnancy rate were comparable in the two groups. These results suggest a negative impact of thyroid autoimmunity in embryo quality in women undergoing ART even when thyroid function is normal.